Thermal conductivity and grain size of ceramic La 1.8-Sr.2- CuO4 - Bekeris, V.; Talpe, J.; Núñez Regueiro, M.; Malachevsky, María Teresa; D’Ovidio, C.; Serafini, D. (Comisión Nacional de Energía Atómica; Argentina)
Fil: Núñez Regueiro, M. Comisión Nacional de Energía Atómica; Argentina